Oncolytic Vesicular Stomatitis Virus: Optimisation Strategies for Anti-Cancer Therapies - Margarita Zinovieva; Anastasia Ryapolova; Alexander Karabelsky; Ekaterina Minskaia (Frontiers in Bioscience-Landmark)
Oncolytic viruses (OVs) represent a targeted anti-cancer therapy approach due to their ability not only to selectively infect and destroy malignant cells but also to induce an immune response. Vesicular stomatitis virus (VSV) offers a promising platform due to its low prevalence and pathogenicity in humans, lack of pre-existing immunity, easily manipulated genome, rapid growth to high titers in a broad range of cell lines, and inability to integrate into the host genome. However, despite its many advantages, many unresolved problems remain: problematic production based on the reverse genetics system, oncological selectivity, and the overall effectiveness of VSV monotherapy. This review will discuss various attempts at viral genome modifications aimed at improving the oncolytic properties of VSV. These strategies include inhibition of viral genes, modification of genes responsible for targeting cancer cells over healthy ones, insertion of foreign genes for boosting immune response, and changing the order of viral and inserted foreign genes. In addition, possible ways to improve VSV-based anti-tumor therapy and achieve higher efficiency will be considered by evaluating the effectiveness of various delivery methods as well as discussing treatment options by combining VSV with other groups of anticancer drugs.